Chasing perfection : a behind-the-scenes look at the high-stakes game of creating an NBA champion - Glockner, Andy (Boston, MA : Da Capo Press, 2016)
"Basketball team building is the ultimate challenge as the NBA level and the last few years have seen a massive change in the amount of money, technology, and approaches to finding and evaluating players. This process starts at the high school level, goes through college, and culminates in the NBA, where the ability to identify and cultivate talent is at an absolute premium. Media and fans like to talk about "busts" when a player doesn't work out, but in truth, it takes a complete team/franchise culture beyond any evaluation system to ensure the greatest chance of player success. Spanning the entire amateur and pro basketball landscape and using the 2014-2015 NBA season as a prism to a much larger story, Chasing Perfection is a fascinating, all-access spin through the inner workings of the smartest minds at every level of the game, all of whom are part of the chase for an end goal that may be impossible: establishing certainty in player acquisition. It is part quant/analysis/data and part philosophical/theoretical, but all interesting. It is about the ongoing, relentless, high-stakes quest to find what national sports writer Andy Glockner calls "Perfected Players" and what ultimately happens to them at the highest (pro) level. Chasing Perfection explores those players who, by the end of their run through high school and college and into the NBA, hit as many qualitative and quantitative predictors of future success as possible"--
Perfected players -- A brief history of modern basketball analytics -- The basketball technology revolution -- Analytics believers and doubters -- The hunt for future perfected players -- Faster, stronger, more explosive -- The tricky art and science of turning data into wins -- How the NBA's best teams were built -- No single path to mining talent -- The world's most perfected player -- The warriors come out to play.
Includes bibliographical references and index.
Keywords: Basketball teams -- United States; Basketball -- United States -- Statistical methods; National Basketball Association -- Forecasting -- Statistics; Basketball -- Economic aspects -- United States; Basketball -- Philosophy